(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses how to overcome the scourge of the disease, which threatens the people of the world today, as easily and lightly as possible, and the use of Alisher Navoi’s ideas to save our youth from the ideological destructions that are spreading around the globe. The author goes into detail that one of the most powerful tools that can affect human health is the word.